Analisis kritis materi IPS dalam pembelajaran IPAS Kurikulum Merdeka - Fatimah, Sri Wahyu; Wardhani, Kristi; Ardhian, Trio (Universitas Sarjanawiyata Tamansiswa, 2025)
This study is motivated by the importance of integrating Social Studies (IPS) content into the Science and Social Studies (IPAS) subject under the Merdeka Curriculum. The research focuses on analyzing the alignment of Social Studies material in Grade IV IPAS learning with the learning outcomes, learning objectives, and learning objective pathways, as well as identifying the scope of Social Studies content taught. This qualitative research involved the principal, Grade IV teachers, and Grade IV students at SD Negeri Gedongtengen Yogyakarta during the second semester of the 2023/2024 academic year. Data were collected through observation, interviews, and documentation, and analyzed using an interactive model consisting of data collection, data reduction, data display, and conclusion drawing. Data validity was ensured through triangulation. The findings indicate that Social Studies content in IPAS learning is appropriately aligned with the learning outcomes, learning objectives, and learning objective pathways, particularly in Chapter 5 Topics B and C. The material includes relevant geographic and economic aspects contextualized to students’ daily lives, enhancing conceptual understanding. The scope of Social Studies content in IPAS at SD N Gedongtengen includes geography, sociology, history, and economics, all of which are integrated meaningfully into classroom instruction.